Unveiling antiplasmodial alkaloids from a cumulative collection of Strychnos extracts by multi-informative molecular networks - Bonnet, Olivier; Beniddir, Mehdi A.; Champy, Pierre; Degotte, Gilles; Mamede, Lúcia; Desdemoustier, Pauline; Ledoux, Allison; Tchinda, Alembert Tiabou; Angenot, Luc; Frédérich, Michel (Frontiers in Molecular Biosciences, 2022)
Malaria, a disease known for thousands of years and caused by parasites of the Plasmodium genus, continues to cause many deaths throughout the world today, particularly due to the emergence of parasite resistance to the current therapeutic arsenal. Plants of the Strychnos genus, remarkable due to their multiple traditional uses as well as their alkaloid content, are promising candidates to develop new antimalarial treatments. Indeed, previous research on this plant group has shown promising (≤ 5 µg/mL) or good (between 5 and 15 µg/mL) antiplasmodial activities. Using the chloroquine-sensitive strain of Plasmodium falciparum (3D7), and artemisinin as positive control, a screening of antiplasmodial activities from 43 crude methanolic extracts from 28 species of the Strychnos genus was carried out in 3 independent assays. A total of 12 extracts had good (6 extracts) or promising (6 extracts) antiplasmodial activities. These results allowed both to confirm known activities but also to detect new ones. These extracts were then analyzed by HPLC-ESI(+)-Q/TOF, and the processed MS/MS data allowed to generate a molecular network in which the antiplasmodial activities were implemented as metadata. The exploration of the molecular network revealed the presence of alkaloids still unknown, and potentially active against malaria, in particular alkaloids close to usambarensine and its derivatives. This study shows that the emergence of molecular networking offers new leads for identifications of alkaloids from the Strychnos genus. The presence of unknown alkaloids potentially active against malaria confirms all the interest to continue in studying the Strychnos genus. Bioassay- and mass-guided fractionations as well as various dereplication tools would allow to identify and characterize these interesting alkaloids further.